PENGARUH KINERJA KEUANGAN DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN CORPORATE SOSIAL RESPONSIBILITY DAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI - Imron, Galih Syaiful; Hidayat, Riskin; Alliyah, Siti (potensio, 2013)
This research aims to test the effect of financial performance and firm size to firm value with Corporate Social Responsibility (CSR) and Good Corporate governance (GCG) as a moderating variable. Sample in this research is the firm of manufacture which enlist in Indonesia Stock Exchange from periode 2008 to 2010, obtained sample is 28 sample with 84 observation. The data analysis used is regression analysis moderation. Results of research refer that the financial performance have an influence on positive to firm value and the size have an influence to firm value. CSR is not able to strengthen relation the financial performance with firm value, but able to strengthen relations firm size with firm value. While GCG able to strengthen relation the financial performance and firm size with firm value. Keyword: Corporate Social Responsibility, Good Corporate Governance, firm size, firm value, financial performance